2016
DOI: 10.1021/jacs.6b01878
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Reorientational Dynamics of Leucine at the Air–Water Interface

Abstract: Ultrafast dynamics of protein side chains are involved in important biological processes such as ligand binding, protein folding, and hydration. In addition, the dynamics of a side chain can report on local environments within proteins. While protein side chain dynamics have been probed for proteins in solution with nuclear magnetic resonance and infrared methods for decades, information about side chain dynamics at interfaces is lacking. At the same time, the dynamics and motions of side chains can be particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
(113 reference statements)
1
24
0
2
Order By: Relevance
“…NMR and neutron scattering experiments, by probing the average atomic motion, shows that the dynamic and the structure of the water in the hydration shell is quite different from the bulk water [18][19][20][21][22][23][24]. The simulations indicate that the water in the protein hydration shell exhibits not only a slower mobility but also a heterogeneous dynamics with a sublinear diffusion [25].…”
Section: Introductionmentioning
confidence: 97%
“…NMR and neutron scattering experiments, by probing the average atomic motion, shows that the dynamic and the structure of the water in the hydration shell is quite different from the bulk water [18][19][20][21][22][23][24]. The simulations indicate that the water in the protein hydration shell exhibits not only a slower mobility but also a heterogeneous dynamics with a sublinear diffusion [25].…”
Section: Introductionmentioning
confidence: 97%
“…13,21,27,[33][34][35] Previously, interface-specific time-resolved vibrational spectroscopy has helped unveil the orientational dynamics of a monomeric leucine amino acid at the air/water interface. It was shown that the methyl units reoriented diffusively on a time scale of 20 ps with diffusivities of D j = 0.07 rad 2 ps À1 in the plane of the surface and D y = 0.05 rad 2 ps À1 out of plane 36 (see Scheme 1 for definition of angles). Here we report on how the folding of the peptide backbone affects ultrafast motions by following the dynamics of leucine side chains in LK peptides with different folds at the air/water interface using time-and polarization-resolved sum-frequency generation spectroscopy (TPSFG).…”
mentioning
confidence: 99%
“…[50a,b, 51] This combination of theory and experiment has enabled the study of very large proteins on complex surfaces.T his has led, for instance,t oamajor advance in the understanding of the biogenesis and maintenance of thylakoid membranes by showing how the IM30 protein, shown in Figure 4, is oriented at the membrane surface to trigger membrane fusion in cyanobacteria and chloroplasts. [52] Then ext challenge in the field will be the observation of protein motions and dynamics.Avery first step in this direction has been the execution of sub-picosecond timeresolved SFG experiments to directly quantify the reorientation of an amino acid side chain at an interface [53] and the energy transfer within the hydration shell of ice-nucleating bacteria. [54] Future developments will be directed towards the Finally,protein adsorption on highly curved surfaces is,in many instances,m ore relevant than adsorption on planar surfaces.O ne advantage of SHG and SFG is that these methods do not necessarily require planar interfaces;infact, they can be carried out in scattering mode,thus allowing the observation of interactions of molecules with nanoparticles in solution.…”
Section: Methodsmentioning
confidence: 99%